2020
DOI: 10.1016/j.carbon.2019.10.075
|View full text |Cite
|
Sign up to set email alerts
|

PMMA-grafted graphene nanoplatelets to reinforce the mechanical and thermal properties of PMMA composites

Abstract: In order to realise the potential of graphene nanocomposites it is vital to control the degree of dispersion and achieve a strong graphene/polymer interface. Herein, we developed a facile 'grafting to' functionalisation approach for graphene nanoplatelets. NH2-terminated graphene nanoplatelets (NH2-GNPs) prepared by a diazonium coupling were used as a 'platform' to covalently graft PMMA chains to the surface of graphene through an amidation between the -NH2 groups and PMMA chains (PMMA-NH-GNPs). A degree of PM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…These findings indicate that BCB doped PMMA films did not incur any degradation or defragmentation upon exposure to high power incident laser irradiation. 64,65 Mechanical properties Tensile testing is one of the most widely used mechanical tests in polymers. 3,65,66 It serves to find some efficient mechanical parameters such as Young's modulus, tensile strength and elongation at break.…”
Section: Ac Conductivitymentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicate that BCB doped PMMA films did not incur any degradation or defragmentation upon exposure to high power incident laser irradiation. 64,65 Mechanical properties Tensile testing is one of the most widely used mechanical tests in polymers. 3,65,66 It serves to find some efficient mechanical parameters such as Young's modulus, tensile strength and elongation at break.…”
Section: Ac Conductivitymentioning
confidence: 99%
“…64,65 Mechanical properties Tensile testing is one of the most widely used mechanical tests in polymers. 3,65,66 It serves to find some efficient mechanical parameters such as Young's modulus, tensile strength and elongation at break. Figure 14 depicts a set of stress-strain curves for pure PMMA and BCB dye doped PMMA films.…”
Section: Ac Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The drug loading and release experiment indicated that this hydrogel could be used to control drug release efficiently. Modification with 4-amino benzene diazonium salt was performed to improve the compatibility of graphene nanoplatelets with polymer matrix by strong covalent filler-polymer interactions [73]. Thus, diazonium modification allows the incorporation of amino groups, which take part in the polymerization of PMMA through amidation between the amino groups and PMMA chains (Fig.…”
Section: Diazonium-modified Graphene/poly(acrylic Acid) Hydrogel Compmentioning
confidence: 99%
“…Fullerene Sulfonated polyether ether ketone Non-covalent [65] Graphene Bismaleimide Covalent [66] Epoxy resin Covalent [67] Poly (acrylic acid) Covalent [68] Polyaniline Non-covalent [69] Polybenzimidazolium Non-covalent [70] Poly(ether ether ketone) Non-covalent [71] Polyimide Non-covalent [72] Polymethyl methacrylate Covalent [73] Polypyrrole Covalent [74] effect of the modified filler on improving properties of composites has also been extensively described.…”
Section: Introductionmentioning
confidence: 99%